Pengenalan Teknologi Digital untuk Media Promosi - Hadi Syahputra; Sri Rahmawati; Surmayanti (Majalah Ilmiah UPI YPTK, 2021)
The digital era that is all internet or the cool term IoT (Internet of things), makes it like it or not, every school must take advantage of these opportunities and challenges. Digital technology is one that has an important role in all aspects that are starting to shift in the world of digitalization. The introduction of digital technology in the school environment is the right step for schools to reach wider targets, so it is possible to get students easily. In addition, digital promotion is also very supportive in improving school branding by utilizing various social media platforms and digital marketing applications. So that the Semen Padang Vocational School will be more widely known by the wider community, both within the region and outside the region though. This student talent development training program by utilizing digital technology aims to invite students to recognize their potential so that they are able to produce works and contribute to the school and its social environment. This training program was given to 30 students consisting of several majors at SMK Semen Padang. The results of the training showed that there was an understanding of students about the importance of gaining new knowledge, especially the use of digital technology in the use of social media to promote activities in schools. With digital promotion technology, it can introduce the quality of education and the quality of school facilities so that junior high school graduates can be interested in continuing their education at SMK Semen Padang.